Atmospheric conditions of extreme precipitation events in western Turkey for the period 2006-2015 - AKKOYUNLU, BÜLENT OKTAY; TAYANÇ, METE (COPERNICUS GESELLSCHAFT MBH, 2019)
This paper investigates the precipitation types and background physical mechanisms of extreme precipitation events (EPEs) over western Turkey during the period 2006-2015. The EPEs are described as the precipitation values above the 90th percentile obtained from the hourly precipitation dataset, which has high spatial resolution. Precipitation types associated with EPEs are identified by using radar outputs and the Lamb weather type (LWT) approach. It is found that EPEs occurred more frequently in the Marmara and Aegean regions during autumn and winter months. In Marmara, mainly 21 %, 17 %, and 15 % of total autumn EPEs show convective, cyclonic, and sea-effect precipitation characteristics, respectively. While convective EPEs are seen more commonly in the southern portions, cyclonic and sea-effect-originated EPEs mainly affect the southwest and northeastern parts of Marmara. Among these three precipitation types, convective mechanisms generally produce more intense daily precipitation (66 1 mm on average) in the Marmara Region under the proper synoptic conditions (highpressure center over the Balkan Peninsula and low-pressure center over the eastern Mediterranean). Based on the hourly observations, convective types of extreme precipitation (EP) show two peak values during afternoon and evening times of the day and are linked to diurnal heating. In terms of the Aegean Region, cyclone-originated EP, which includes 65 % of the total winter EPEs, is more common in the whole territory and reaches its peak value during the early hours of the day.
Keywords: CONVECTIVE SYSTEMS; CIRCULATION TYPES; UNITED-STATES; FLASH-FLOOD; RAIN EVENTS; CLIMATOLOGY; PATTERNS; SOUTHERN; REGION; COAST